Research on multi objective planning optimization of integrated energy system with economic and low carbon objectives - Chen Rong; Jia Zejun; Wang Yongli; Huang Feifei; Ma Yuze; Han Xu (E3S Web of Conferences, 2020)
In response to the global energy crisis, the integrated energy system has become an important part of the energy revolution. Aiming at the economic operation of the Integrated Energy System (IES), this paper proposes a system optimization planning model that takes the economic and environmental optimization as the goal and establishes a coupled capacity planning system, and jointly optimizes the capacity configuration and configuration of a single energy supply module. Power output to pursue maximum benefit. In order to illustrate the advantages of this method, on the basis of simulation, a dynamic programming method is used to solve the model. Finally, the simulation results show the effectiveness of the planning optimization model proposed in this paper, and provide a new path for solving the optimization problem of integrated energy system planning.